KETAHANAN KELUARGA BURUH MIGRAN DI KARANG PAKIS, NUSAWUNGU, CILACAP - Muchimah, Muchimah (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2020)
AbstractThis paper discusses how the migrant family workers maintaining their household affairs despite the difficulties of having long distance relationship. The object of this research are the migrant family workers in Karang Pakis, Nusawungu District, Cilacap Regency. This descriptive-analytic empirical research functions social action of Talcott Parsons . The result shows that the migrant workers' families adapt to their problems by having communication with their partners, keeping themselves busy, and taking the role of a partner. The goal attainment that were realized are improving the family economy, renovating and completing the furnishings of the house, owning a car, preparing a better generation and improving spiritual quality. Pattern Maintenance (latency), by maintaining the existing pattern while being left out by their partner. The contribution of this paper shows that the families of migrant workers do not always end in divorce. This is evidenced by the situation in the village of Karang Pakis where the families of migrant workers are able to maintain and try to change the economy of their families by committing each other for the sake of family happiness in the future.Problem dalam keluarga buruh migran sering terjadi karena salah satu pasangan ada yang pergi bekerja ke luar negeri meninggalkan keluarga. Anggota keluarga buruh migran di Karang Pakis Kecamatan Nusawungu Kabupaten Cilacap berupaya mempertahankan keutuhan keluarganya. Tulisan ini membahas tentang bagaimana cara menjaga keutuhan keluarga buruh migran di desa Karang Pakis Kecamatan Nusawungu Kabupaten Cilacap. Penelitian empiris yang bersifat deskriptif-analitik ini memanfaatkan teori tindakan sosial Talcott Parsons. Cara keluarga buruh migran beradaptasi yaitu dengan melakukan komunikasi dengan pasangan, menyibukkan diri, dan mengambil peran pasangan. Goal Attainment yang terealisasikan diantaranya untuk memperbaiki perekonomian keluarga, merenovasi dan melengkapi isi rumah, memiliki mobil, mempersiapkan generasi yang lebih baik serta meningkatkan kualitas spiritual. Pattern Maintance (latensi), dengan cara memelihara pola yang ada selama ditinggalkan oleh pasangan mereka. Kontribusi tulisan ini menunjukkan bahwa keluarga buruh migran tidak selalu berakhir dengan perceraian. Hal ini dibuktikan dengan keadaan yang ada di desa Karang Pakis. Dimana keluarga buruh migran mampu menjaga dan berusaha untuk merubah perekonomian keluarga mereka dengan saling berkomitmen antar pasangan demi kebahagiaan keluarga ke depannya.